Creating a Continuing Education Pathway for Newly Arrived Immigrants and Refugee Communities - Aster S Tecle (2023)
With the increase in the number of displaced peoples, the demand for skilled social workers from diverse backgrounds to serve them is critical. This article explores a continuing education program that prepares precollege individuals from newly arriving communities who will work as entry-level workers serving these immigrant and refugee communities. The article focuses on the development of a Case Management Certificate Program as a response to community-identified issues, then presents a discussion exploring the educational pathways and unique contributions of these individuals. The article calls for the profession to explore how continuing education pathways can bridge service gaps, contribute to the knowledge base of social work, and meet current labor market demands.